Urban built environment and its impact on university students’ loneliness: a mechanistic study - Deng, Shuguang; Su, Jinhong; Yang, Heping; Liang, Jinlong; Zhu, Shuyan (Frontiers in Public Health, 2025)
IntroductionWith the acceleration of urbanization and social changes, loneliness among university students is becoming increasingly common. The urban built environment is closely related to loneliness. This study explores the impact of the urban built environment on the loneliness of university students from multiple built environment elements such as road network density, land use mix, and service facilities. It is of great significance to optimize urban planning and improve the mental health of university students.MethodsBased on questionnaire data and point interest data of various facilities, Spearman correlation analysis, Ridge regression model and geographic detector were used to explore the impact mechanism of urban built environment on loneliness of university students.ResultsThe study shows that loneliness is widespread and relatively severe among university students. The urban built environment is closely related to university students’ loneliness: the number of catering, transportation, tourist attractions, leisure and entertainment, healthcare, and sports facilities, as well as road network density, are significantly negatively correlated with loneliness, while the number of shopping facilities and land use mix are positively correlated with loneliness. Geographic detector analysis shows that tourist attractions, health care facilities and land mix have a significant impact on university students’ loneliness, and the interaction of multidimensional factors significantly improves the explanatory power of loneliness.ConclusionTo alleviate loneliness among university students, interventions should be approached from the perspective of urban planning and management. Firstly, it is essential to improve leisure, landscape, transportation, healthcare, and fitness facilities, enhancing their accessibility to foster social interactions. Secondly, increasing the availability of socially-oriented public spaces, such as student activity centers, community squares, and shared learning spaces, can strengthen interaction and communication. Additionally, policymakers should optimize the layout of urban transportation networks to encourage students to use public transit. Urban planners can support active transportation modes, such as walking and cycling, by rationally allocating road space. Lastly, the strategic placement of green and open spaces, such as parks and squares, should be prioritized to enhance access to natural environments, promote social activities, and mitigate feelings of loneliness.